The impact of the patient macroenvironment on molecular subgroups in endometrial cancer - Werner, Henrica M. J.; van Dijk, Frederiek A. H.; Vrede, Stephanie W.; van den Bosch, Anouk A. S.; Lombaers, Marike S.; Asberger, Jasmin; Huvila, Jutta; Snijders, Marc; Tubita, Valeria; Moreno Mancebo, Gemma; Matias-Guiu, Xavier; Bretová, Petra; et al. (Wiley, 2026)
More than half of endometrial cancer diagnoses can be attributed to obesity. A purely molecular classification in endometrial cancer hampers further understanding of the impact of patient macroenvironment as a major risk factor. The relationship between patient factors, such as age, body mass index (BMI), comorbidity, and ethnicity, and molecular subgroups was studied in a publicly available data set (N = 225) and two multicenter European cohorts (N = 223; N = 946). Age at diagnosis was highest in the TP53-mutated subgroup, and differed significantly between molecular subgroups. Patients with obesity were younger at diagnosis compared to their lean counterparts across all molecular subgroups (61.9 vs. 66.2 years; p <.01). Survival was worst in the TP53-mutated subgroup but improved with increasing BMI, which resulted in nonsignificant differences from other subgroups when BMI was >35. These data underscore that patient factors remain important, and their integration with molecular factors needs to be better understood to ultimately improve treatment and prevention strategies in endometrial cancer.